How weather conditions affect guest arrivals and duration of stay: An alpine destination case. (29th April 2021) - Bausch, Thomas; Gartner, William C.; Humpe, Andreas
Abstract: Weather can be a major concern for travelers when choosing a destination, preparing their trip and during their stay. Existing publications focus on explaining the role of weather based on one, or at most, a few parameters and usually for one season. This paper proposes a new approach covering all four seasons by connecting daily data from meteorological stations to tourists' registration information. This approach allows for an understanding of travel volumes based on actual travel data and not on perceptions or desired outcomes. The results suggest a clear impact of weather on the number and duration of short‐term trips for all seasons. There was no clear indication that weather forecasts played a significant role in the structure of mid or long term trips.